2023
DOI: 10.1111/clr.14118
|View full text |Cite
|
Sign up to set email alerts
|

Influence of abutment macro‐ and micro‐geometry on morphologic and morphometric features of peri‐implant connective tissue

Abstract: ObjectivesThe aim of the present human observational study is to provide morphologic and morphometric analysis of peri‐implant connective tissue next to abutments with divergent or convergent macro‐geometry and different surface micro‐characteristics.Materials and MethodsThirty patients were rehabilitated with single implants in the posterior area and one out of three different healing abutments with a one‐stage technique: machined divergent abutment (DIV‐MAC), machined convergent abutment (CONV‐MAC) or conver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…These observations and exploratory hypotheses were confirmed in Ref. [25]: in this human observational study it was provided morphologic and morphometric analysis of peri-implant connective tissue next to abutments with divergent or convergent macrogeometry and different surface micro-characteristics. Convergent abutment profiles, regardless of their surface microgeometry, were observed to favor axial development of peri-implant connective tissue.…”
Section: Regenerative Medicinesupporting
confidence: 62%
“…These observations and exploratory hypotheses were confirmed in Ref. [25]: in this human observational study it was provided morphologic and morphometric analysis of peri-implant connective tissue next to abutments with divergent or convergent macrogeometry and different surface micro-characteristics. Convergent abutment profiles, regardless of their surface microgeometry, were observed to favor axial development of peri-implant connective tissue.…”
Section: Regenerative Medicinesupporting
confidence: 62%
“…While many authors have reported on the importance of the characteristics of the fixture-abutment interface on the level and loss of peri-implant bone tissue [35], few studies have examined the structure and ultrastructure of human peri-implant soft tissues [7,11,[13][14][15][16]. The 3D networks of collagen bundles that compose the connective portion have been found to be transversely and longitudinally oriented in relation to the dental implant axis.…”
Section: Discussionmentioning
confidence: 99%
“…The 3D networks of collagen bundles that compose the connective portion have been found to be transversely and longitudinally oriented in relation to the dental implant axis. During the growth of these bundles, they organize themselves into intertwining patterns [13][14][15] with different quantitative distributions depending on time from surgery, environmental conditions, and implant macro-and micro-geometry; these boundary conditions are currently the focus of several studies [7,11,[13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was demonstrated that synchrotron phase-contrast imaging is capable of studying 3D parameters that cannot be analyzed with histologic techniques but are important to define the 3D microarchitecture of the collagen bundles and the 3D structural complexity of connective tissues. Remaining in the same research field, Canullo et al [40] performed an in-depth study on the impact of the implant macroand micro-geometry on peri-implant connective tissues, most likely linked to the contact force at the interfaces between soft tissues and abutment.…”
Section: Neck and Odontostomatological Regionsmentioning
confidence: 99%